Refitting a patient with pellucid marginal degeneration from a corneal rigid gas permeable lens to scleral lens - Lundanes, Eilin; Gustafsson, Jörgen (Scandinavian Journal of Optometry and Visual Science, 2020)
This case report describes a 66 years old male patient with pellucid marginal degeneration (PMD). The patient had fallen out of a regular follow-up scheme and presented with a poorly fitting corneal rigid lens that he had worn for almost five years. Correction had failed to improve vision in the left eye, so the patient wears a contact lens in his right eye only. Scleral lenses vault over the cornea, the tear layer between the lens and the cornea masks corneal irregularities and are a good correction option for corneal ectasias. This patient was fitted with an Onefit scleral lens that provided good visual acuity and comfort. Lens handling was no obstacle to this patient. A heart surgery postponed the first follow-up examination. Follow-up examination 8 months after the refit resulted in no changes of lens parameters as the fitting was still acceptable and the patient was happy. Attention to the inferior limbal clearance will be the focus at the next follow-up in 6 months’ time.